Gold Dinar as medium of transaction among Muslim countries : a fiqh perspective - Ayinde, Olorogun Lukman (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
Money in the form of hard currency was introduced in ancient times to overcome the obstacles posed by barter trade. Instead of goods being exchanged for goods with an approximately equal value, goods were bought and sold in the form of gold, silver or other precious metals. Only in later times, coins which worth their actual value were replaced by paper money, and their value guaranteed by the public treasuries of the issuing countries. These modern forms of currency are the basis of modern economies all over the world, the developed and the developing alike. Muslim countries are generally classified as 'emerging markets' based on the exchange power of their currencies on international markets. Following the lobbyists of leading economic countries – through their posited institutions such as IMF and World Bank -- the US dollar and European Euro form the major currencies while other currencies – among them the 58 OIC countries -- have been relegated to serving only as ordinary domestic means of transactions. The governments of all 58 Muslim countries are currently using US dollar and Euro in their international transactions. Fatwas issued on the permissibility of relying on foreign – and more importantly non-Muslim – currencies. This research aims to re-evaluate such an alleged permissibility based on independent reasoning (ijtihad) and the reinterpretation of the revealed text (Qur'an). The researcher discovered that their interpretations and applications of the revealed text with regard to the permissibility of foreign currency exchanges are untenable and go against Islamic compliant transactions. There exist numerous contradictory Islamic legal rulings which have no basis in the Qur'an and Sunnah forwarded by some scholars of Islamic Law to justify their position. The researcher concludes with a call to establish the Gold Dinar as a legitimate means of foreign exchange for Muslim economies. Muslim states have the obligation to emancipate themselves from their lamentable dependence on Western countries.